If it's not what You are looking for type in the equation solver your own equation and let us solve it.
20=4(y+3)-6y
We move all terms to the left:
20-(4(y+3)-6y)=0
We calculate terms in parentheses: -(4(y+3)-6y), so:We get rid of parentheses
4(y+3)-6y
We add all the numbers together, and all the variables
-6y+4(y+3)
We multiply parentheses
-6y+4y+12
We add all the numbers together, and all the variables
-2y+12
Back to the equation:
-(-2y+12)
2y-12+20=0
We add all the numbers together, and all the variables
2y+8=0
We move all terms containing y to the left, all other terms to the right
2y=-8
y=-8/2
y=-4
| 6a+2/9=3a-1/4 | | 6x-2=2(2x+1)+2x-4 | | (k/4)=8 | | 3(y-4)-4=-5(-4y+4)-5y | | -5(2x-1)+4(3x-2)=-6(x+3) | | Y=25x=16 | | (X-2)^2-2(x-2)-15=0 | | x(3x-6)+2x(x-3)=36+x^2 | | 7x+36=16x | | 7/10x+2= | | 324t^2-360t=0 | | 1/3x-21=32 | | 22=2-y | | 12.95p=44 | | -3(3x+15-(10+x)=35 | | 3.2h-8=h+17 | | y-2=3+2y | | -2(3y-3)+2y=8+2(6y-2) | | 12x+34+6x=46x-29 | | 2x-3+5×+2=90 | | F(n)=-3(n-1);-51 | | 9w-16.5=5.3 | | 2x+5=x/8 | | 5x2/3-10x=0 | | -n/3+10=21 | | -5y-1=-60 | | 16=–d+6 | | 2/3x-1/2=5/6x+2 | | 3x-23=7+9 | | 3x+6(x+4)=-21 | | 4x-8(0,8)=40 | | 2x/1-1=10 |